2013
DOI: 10.1002/elps.201200587
|View full text |Cite
|
Sign up to set email alerts
|

Electromembrane extraction: Distribution or electrophoresis?

Abstract: This paper presents for the first time a phenomenological theoretical model for the time dependent distribution of analytes during electromembrane extraction (EME). The model was verified experimentally for a range of model drugs and peptides. Analytes were extracted from an acidified aqueous sample solution, through an organic supported liquid membrane (SLM), and into an acidified aqueous acceptor solution. Mass transfer was governed by an applied electric field across the SLM. A rapid depletion was seen in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 32 publications
(34 reference statements)
1
44
0
Order By: Relevance
“…Several studies have described and discussed theoretical models for mass transfer in EME . The proposed models are based on assumptions to simplify the final mass transfer equations.…”
Section: Mass Transfer In Eme From a Theoretical Point Of Viewmentioning
confidence: 99%
“…Several studies have described and discussed theoretical models for mass transfer in EME . The proposed models are based on assumptions to simplify the final mass transfer equations.…”
Section: Mass Transfer In Eme From a Theoretical Point Of Viewmentioning
confidence: 99%
“…Solution resistance, R sol As described in previous works [11,23], the applied potential in EME is distributed between donor/acceptor solutions and SLM. According to Ohm's law, the portion of the applied potential that drops in the donor solution is proportional to the solution resistance:…”
Section: Resultsmentioning
confidence: 99%
“…All these stock solutions were stored at À 32 1C and protected from light [26,28]. The sample for the extraction process (step 1) was obtained daily by diluting the stock solutions with 25 mM phosphate buffer with a pH of 3.50.…”
Section: Preparation Of Solutionsmentioning
confidence: 99%
“…Up to date, a few research articles have reported EME of peptides with the hollow fiber EME format [17,18,[22][23][24][25][26]. However, high system-current and low recoveries for the peptides have been the main challenges [6,19].…”
mentioning
confidence: 99%